A finite element correction method for sub-20 nm nanoindentation considering tip bluntness. (15th December 2017) - Zhang, Youfeng; Wang, Hongbo; Li, Xinwei; Tang, Huan; Polycarpou, Andreas A.
Abstract: Due to substrate effects and inherent tip bluntness, using current state-of-the-art nanoindentation instrumentation, it is difficult to directly measure mechanical properties of thin films less than 20 nm thick. With the aid of Finite Element Analysis (FEA), we obtain the mechanical properties by correlating simulated force-displacement responses with those from nanoindentation experiments. For shallow indentation experiments that is required for very thin films, it is found that an indenter model with a blunt tip is more realistic and leads to accurate characterization of mechanical properties. The proposed blunt tip model is validated with experiments on a standard fused quartz sample, and then applied to measure the nanomechanical properties of a 90 nm thick metal alloy layer and a 14 nm thick magnetic layer sandwiched between a carbon overcoat and a metal alloy. The magnetic layer properties are found to be 180 GPa for the reduced modulus and 2.9 GPa for the yield strength.